The Role of Triglyceride Lipase, Fatty Acid Synthase and Fatty Acid Binding Protein Family Genes on Fat Metabolism of Broiler Chickens - Niken Ulupi; C Sumantri (Indonesian Center for Animal Research and Development, 2015)
Broiler chicken has high fat content, especially abdominal and subcutan fat which reduced carcass quality and efficiency of feed energy. Genetic approach could be potentially applied to reduce high abdominal and intramuscular fat in broiler chicken through the selection program at gene level related to fat metabolism. This paper describes the metabolism and biosynthesis of body fat and the role of its controlled genes. Fat synthesis is controlled by feed quality and metabolism and biosynthesis process occurred in liver. These processes are controlled by many family genes, but certain genes have dominant role in the process; those are triglyceride lipase genes, fatty acid synthase genes and fatty acid binding protein genes. Expression of fatty acid synthase genes has positive correlation with fat content in liver and intramuscular. Expression of fatty acid binding protein genes was related to the increased abdominal fat deposit. These genes are polymorphic, so that they can be used as a genetic marker in selection to optimize feed efficiency, to minimize abdominal fat and to increase economic value of broiler chicken. Key words: Fat, triglyceride lipase genes, fatty acid synthase genes, fatty acid binding protein genes